Investigation of the cogging factor of CMG and RPMG for several pole pair combinations - Mohd Ab Halim, Mohd Firdaus; Sulaiman, Erwan; Ab Rahman, Azhan (TUBITAK, 2023)
: The design of magnetic gear (MG) involves determining the gear ratio specific to its application. The gear ratio can be determined by the pole number of the inner rotor, outer rotor, and pole piece. This research investigates the cogging torque of several pole pair combinations in concentric magnetic gear (CMG) and rotating pole piece magnetic gear (RPMG). The gear ratio equations are initially derived for both the CMG and RPMG. Based on these equations, four sets of pole pair combinations are determined. The cogging factor is calculated in each combination. To determine the cogging factor significance towards the cogging torque, the magnetic gears are simulated in 2D finite element software. The result revealed that the lower pole pair combination generates 6 % to 9 % lower cogging torque than the higher pole pair combination. The simulation result also shows that the rate of increase in cogging factor did not correlate directly to the cogging torque in the simulation. It can be concluded that the cogging factor is not a suitable tool to assess the cogging torque level in CMG and RPMG.